Development Of Dissimilar Micro Friction Stir Welding Copper With Alumniumum Plate - Hakam Muzakki; Teguh Prasetyo; Ahmadi; Ayub Brahma Kurnianto (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Friction welding as joining method has a good joining condition. The results of FSW welding have the advantage that the surface is smoother and flatter than the results of arc welding. Friction rotary welding includes several stages, namely material welding and microstructural analysis. In this study the material welding was used copper and aluminum alloy 1100 with sizes 60mm, 50mm, 0.5mm and macro structural analysis using a digital microscope. Experiments were carried out using lap joints with dimensions of 100mm, 50mm, 0.5mm with variations in loading parameters of 30kgf, 40kgf, 50kgf and variations in shoulder diameters of 4mm, 6mm, 8mm. In the experiment, the larger the diameter of the shoulder, the greater the loading required to connect the two materials, but if the loading is too large, it can cause defects in the welding results. The welding results at the welding pressure parameter of 40kgf with a shoulder diameter of 8mm show that welding with these parameters is capable of performing welding because the areas of the welding results are evenly connected and there are no holes (hooks) in the welding results. The results of welding at a welding pressure parameter of 50kgf with a shoulder diameter of 8mm show that the results of joining the copper and aluminum are mixed evenly but damage the surface of the copper. The macro structural results show that the welding pressure affects the shoulder diameter, if the welding pressure is too large and the shoulder diameter is too small it will only damage the copper and aluminum material because it only has a thickness of 0.5 mm, and vice versa if the welding pressure is too small and the shoulder diameter is too large, the two materials cannot be connected. In this study, the best results were obtained with a shoulder diameter of 4mm and a pressure of 40kgf because there were no defects or holes in the welding results.